How a Tutor Uses Gesture for Scaffolding: A Case Study on L2 Tutee's Writing. Issue 2 (17th February 2017) - Kim, Suyeon; Cho, Sookyung
Abstract : Recently, from the Vygotskyan socio-cultural perspective, second language (L2) researchers have paid growing attention to scaffolding and have argued that L2 learning is enhanced through experts' scaffolding. However, not much is known about how teacher gesture scaffolds L2 learners' writing and how teachers manipulate writing-oriented gestures (i.e., writing gestures and gestures interacting with pen and paper) for L2 scaffolding. Therefore, we conducted a descriptive case study to examine how one writing tutor utilizes gesture and manipulates pen and paper to scaffold the L2 writing of a college student at a low proficiency level. We video-taped, transcribed, and coded one 30 minutes' writing session. We found that the tutor employed gesture primarily for instructional scaffolding to explain L2 vocabulary or grammar to the learner and help her self-repair. The tutor also used gestures involving pen and paper to scaffold the L2 tutee's writing performance, elicit more engagement, and eventually establish intersubjectivity.